2019
DOI: 10.2967/jnumed.119.230961
|View full text |Cite
|
Sign up to set email alerts
|

Total-Body PET and Highly Stable Chelators Together Enable Meaningful 89Zr-Antibody PET Studies up to 30 Days After Injection

Abstract: See an invited perspective on this article on page 451. The use of 89 Zr-antibody PET imaging to measure antibody biodistribution and tissue pharmacokinetics is well established, but current PET systems lack the sensitivity needed to study 89 Zr-labeled antibodies beyond 2-3 isotope half-lives (7-10 d), after which a poor signal-to-noise ratio is problematic. However, studies across many weeks are desirable to better match antibody circulation half-life in human and nonhuman primates. These studies investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 27 publications
3
82
0
Order By: Relevance
“…The results of this study indicated that DFOSq had better stability in vivo and an improved tumor to background imaging quality than DFO-NCS (Rudd et al 2016). In addition, recent data indicate that DFOSq has an improved shelf life compared to DFO-NCS (Berg et al 2020). Hence, since we intended to employ DFOSq as the bifunctional chelator for conjugating chDAB4 in a future clinical study, we wished to test its attributes for this task in comparison to the industry standard, DFO-NCS.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study indicated that DFOSq had better stability in vivo and an improved tumor to background imaging quality than DFO-NCS (Rudd et al 2016). In addition, recent data indicate that DFOSq has an improved shelf life compared to DFO-NCS (Berg et al 2020). Hence, since we intended to employ DFOSq as the bifunctional chelator for conjugating chDAB4 in a future clinical study, we wished to test its attributes for this task in comparison to the industry standard, DFO-NCS.…”
Section: Introductionmentioning
confidence: 99%
“…PET also has higher sensitivity, which is particularly beneficial for patients, as it requires lower radiation doses. A next leap forward herein is the recent introduction of advanced whole-body PET scanners as their larger field of view further increases the sensitivity, resulting in better image quality and more accurate assessment of tracer biodistribution at a low count rate [9,10].…”
Section: Advanced Technology and Applicability Of Molecular Pet Imagimentioning
confidence: 99%
“…In recent years, several molecular imaging techniques, notably nuclear techniques such as Positron Emission Tomography (PET), have been developed that conjoin both diagnostic and theranostic applications to directly link molecular biology with molecular diagnosis and molecular targeted therapy [7,8]. In our review, we appreciate these developments at multiple levels, with special consideration for the added value in the challenging field of neuro-oncology, where PET imaging not only can serve as a sensitive diagnostic tool enabling non-invasive studies of tumor characteristics at multiple sites over time, but can also serve as an in vivo theranostic tool guiding drug development and drug delivery studies by display of target expression and target binding behind the assumedly intact blood-brain barrier (BBB) [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Satisfactory image quality was obtained even at 30 days post injection, representing approximately 9-fold half-lives of 89 Zr to identify the activity of anti-gD IgG in different organs like liver, kidneys, and bone joints ( Fig. 6 ) [ 72 ].
Fig.
…”
Section: Assessment Of Biological Functionsmentioning
confidence: 99%